Pelatihan Keterampilan Otomotif Untuk Mengurangi Pengangguran - Tamara, Adila (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 25 No 1 (2025), 2025)
Unemployment is a serious social problem in many countries, including Indonesia. One effective way to reduce poverty is to provide skills training to individuals who want to work in the automotive industry. This article aims to discuss the importance of automotive skills training in reducing poverty and provide concrete solutions to overcome this problem. The aim of this research is to explore the role of automotive skills training in reducing attrition and increasing employment opportunities for individuals seeking a career in the automotive industry. The research method used is a study of literature relevant to this topic. The research results concluded that through this training, individuals can obtain skills that suit the needs of the automotive industry, thereby increasing their chances of getting a decent job. In addition, automotive skills training also provides economic benefits for individuals and society as a whole.